It's all absolutely fine : life is complicated so i've drawn it instead - Elliot, Ruby (Andrews McMeel Pub., 2017)
Explore the highs and lows of modern life through the sharp, dark wit of Ruby Elliot--creator of the massively popular Tumblr account, Rubyetc, which has over 210k followers and growing. Ruby's simple drawings of not-so-simple issues capture the humor and melancholy of everyday life. Her comics appeal to both new adults who are beginning to explore these subjects and to battle-tested veterans of the daily struggles of life with mental illness